Cover Feature: Doping Graphene into Monodispersed Fe3O4 Microspheres with Droplet Microfluidics for Enhanced Electrochemical Performance in Lithium‐Ion Batteries (Batteries & Supercaps 1/2019). Issue 1 (2nd January 2019) - Liu, Na; Li, Chunlin; Xie, Hua; Liu, Yingjia; Liu, Jiannan; Gao, Jing; Han, Jingfeng; Chen, Jian; Wei, Yingxu; Lin, Bingcheng; Liu, Zhongmin
Abstract : The Cover Feature shows graphene‐doped Fe3 O4 monodispersed microspheres which are fabricated using droplet microfluidic technology. The microfluidic method is found to enhance the electrochemical behaviour of the material when it is employed as the anode in lithium‐ion batteries.More information can be found in the Communication by N. Liu et al.(DOI:10.1002/batt.201800072 ).